Un climat de compétition : le changement climatique comme économie politique dans la fiction spéculative, 1889-1915 - Steve Asselin (ReS Futurae, 2023)
This paper demonstrates how the first major locus of climate-change fiction in the late nineteenth and early twentieth centuries already integrates climate into an economic rhetoric that views climate policy as a zero-sum competition between rival nations. In speculative fiction of the period, climate change occurs principally as a result of largescale human geoengineering projects aimed at transforming the world. Examples of this deliberate anthropogenic climate change include texts by Jules Verne, Mark Twain, and George Griffith. Sf writers found ways to monetize as-yet-unincorporated aspects of nature such as climate as resources for the market economy ; access to resources, in turn, became part of the economic and political balance of power between state entities. Plots to disrupt, control, and monopolize climate were conceptualized as grandiose capitalist schemes capable of unleashing significant collateral damage ; yet many of these novels present geoengineering as laudable entrepreneurship operating out of legitimate economic self-interest. At the extreme, several stories outright weaponize the weather and convert climate change into military might, featuring the same kind of technological brinksmanship that defines an arms race. The economics of early climate change fiction foreshadows, and potentially conditions us, to view climate as a resource worth fighting for.